Reconstructing the Kato Nan Ampek Culture: A Model of Communication Ethics Education to Address the Moral Degradation of Children in the Village of Batang Palupuh, West Sumatra - Hardiyanti, Sri Sundari; Hawari, Muhammad Anas; Agustin, Nabila; Almufid, Ahmad Dzaki; Ar Rahma, Aisyah Zalfaa (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2023)
The moral degradation that occurs among children in Batang Palupuh village, West Sumatra is caused by internal and external factors. The internal factors that cause moral degradation in children are parenting and the shifting role of Tungku Tigo Sajarangan. This research aims to reconstruct Kato Nan Ampek culture as a solution to overcome the moral degradation that has occurred. In this research, the research method used is ethnographic qualitative research. From the results of the research conducted, it was concluded that to overcome moral degradation through Kato Nan Ampek culture, it must begin with parenting and improvements to the role of Tungku Tigo Sajarangan. Then, to better understand the children of Batang Palupuh Village Kato Nan Ampek culture, they were assisted by resolving problems related to external factors, namely the development of science and technology and curriculum changes.